Survival enhancement of probiotic Lactobacillus plantarum CMU-FP002 by granulation and encapsulation techniques - Woraharn S. (2014)
Two processes of enclosure of probiotic Lactobacillus plantarum CMU-FP002, probiotic granules and calcium alginate beads, were studied. Sodium alginate solution at 1.0, 1.5 and 2.0 % (w/v) was used as a binder. The results showed that 20 log cfu/ml initial concentration of cells could be entrapped by the granules and beads with 12 to 13 log cfu/g and 16 cfu/g, respectively. The physical properties of granules and beads revealed that the strength increased when sodium alginate concentration was increased. On the other hand, the dissolution decreased. Probiotic granules completely released the cells within 60 min after being suspended in stimulate gastric fluid (SGF) pH 1.8 and had 2 to 3 log survival cells per gram. Calcium alginate beads, which were formulated from 1.0 and 1.5% (w/v) sodium alginate solution, gradually released bacterial cells and were completely released in SGF within 120 min. The beads formulated from 2.0 %(w/v) sodium alginate solution could not completely release the probiotics. The beads contained more survival cells than granules. Furthermore, the beads formulated from 1.5% (w/v) sodium alginate solution had the highest survival cells (9.30 log cfu/g). Probiotic cells in calcium alginate beads were still high (11 log cfu/g), although they were stored at 4°C for 5 days alternating with room temperature for 5 days, for a total of 2 month. Further application in broilers will be studied. © 2010 Academic Journals.